Comparison between Iranian and German SACH Foot by Gait Analyzer and Dynamometer - T Tahmasebi; E Ebrahimi; A Hassanzadeh (Vesnu Publications, 2008)
Abstract Introduction: Due to high percentage of lower Limb amputations specially traumatic transtibial sections, the application of foot in below knee prosthesis in highly important  are of these foots which are used commonly by prosthetics is SACH foot. The aim of this research is to compare the functional moment and physics of two SACH foot made by Iran and Germany which have the same Strictures. Methods: The study was Performed on 14 male individuals with below knee amputation (25 - 50 years old). After second references of each patient and completing a questionnaire necessary information gathered and recorded by associated instruments such as Gait Analyzer and Dynamometer. Then results were analyzed by paired t-test. Result: It was revealed that velocity of ankle, knee and hip joints in all cases with German prosthesis is highly more than Iranian type. Acceleration of hip joint in first and second part of time in German prosthesis was more but it was not in the third part. Acceleration of knee joint in German type is more only in the second part of movement time. Power distribution in anterior part of German type is significantly less than Iranian rival. Conclusion: The result of this study shows that German prosthesis is superior in forms of power, velocity of acceleration measured by gait analyzer and dynamometry Key Words: SACH foot, prosthesis, gate analyze, dynamometer